Деякі результати локальної теорії гладких функцій - Самойленко, А.М. (Інститут математики НАН України, 2007)
Приведены результати исследования локального поведения гладких функций в окрестностях их регулярных и критических точек, доказаны теоремы о средних значениях рассматриваемых функций типа теоремы Лагранжа о конечных приращениях, исследована симметрия производной аналитической функции в окрестности ее кратного нуля, доказаны новые утверждения подготовительной теоремы Вейерштрасса, касающиеся критической точки гладкой функции конечной гладкости, определено неградиентное векторное поле функции в окрестности ее критической точки и рассмотрен один критический случай устойчивости положения равновесия нелинейной системы. We present results of the investigation of the local behavior of smooth functions in neighborhoods of their regular and critical point and prove theorems on mean values of considered functions similar to the Lagrange theorem on finite increments. We also investigate the symmetry of the derivative of an analytic function in the neighborhood of its multiple zero, prove new statements of the Weierstrass auxiliary theorem related to the critical point of a smooth function of finite smoothness, determine a nongradient vector field of the function in the neighborhood of its critical point, and consider one critical case of the stability of equilibrium position of a nonlinear system.